The impact of information and communications technology (ICT) in the teaching and learning of kinematics in grade 11 physical science. - Arowolo, Kayode Mathews (My University, 2009)
This research examines the impact of information and communications technology (ICT) in the teaching and learning of kinematics, a section of the high school Physical Science syllabus in Grade 11. The use of simulations in Physical Science teaching served as an intervention. These simulations were used to teach Newton‟s laws of motion. In this research, we make use of computer simulations to teach kinematics in Grade 11 in a South African high school. This research uses the constructivist theory of learning which is extended by Vygotsky‟s (1978) social-cultural theory of learning in which a child is helped to attain his level of potential development. The theoretical framework was formulated in accordance with the work of Vygotsky‟s (1978) zone of proximal development (ZPD). The simulation was used by the teacher to help a learner reach the level of potential development. The interaction that arises during the use of the simulations by the teacher can bring about some valuable input that other learners will benefit from when they listen to and contribute to the discussions. We use simulations to help the students reach their level of potential development since they are able to visualize the real world, hence making understanding of the concepts easier. The interaction resulting from the use of the simulations can create opportunities for the learner to transform what they can pick from the inter-psychological, which is between the learner, and the peers or the teacher, to the intra-psychological, which becomes a form of internalised learning (Vygotsky, 1978). A null hypothesis is formulated to help assess the impact on ICT on teaching and learning of kinematics. This is “the use of CAI (independent variable) does not impact on the teaching and learning (students’ achievement) of Physical Science concepts (kinematics)”. The work is guided by the following critical questions: (i) How does CAI influence the performance of Grade 11 learners in kinematics? (ii) How does a teacher embrace the use of ICT in the teaching of kinematics to create a pedagogical change from the traditional modes of instruction (teacher-talk method)? (iii) What are the factors hampering the use of ICT for instructions in Physical Science? The study used a quasi-experimental research design with a control and an experimental class (with 30 students in the experimental class and 26 in the control group) in one South African high school in the Gauteng province as a case. The two classes formed the groups of average ability in the set (Grade 11) and they were so distributed into the classes based on the previous academic performance in the school. Pretest and posttest were conducted to measure the impact of the simulation instruments developed by Interactive Physics and the one developed by the Physics Education Technology (PhET) project based at the University of Colorado at Boulder, Colorado, USA on the performance of the students after the intervention was used in teaching. Classroom observations and post-intervention interviews were conducted to be able to answer research questions 2 & 3. The impact of information and communications technology (ICT) in the teaching and learning of kinematics in Grade 11 Physical Science – Kayode Arowolo v The data collected from the follow-up interview and classroom observation were coded and analysed using atlas.ti scientific software for qualitative data analysis management and model building. Also, the results of the pretest and the posttest were analysed using t-test and statistical analysis tool available in Microsoft Excel. Analysis of the pre-test scores shows no statistically significant difference (p > 0.05) in the performance of the two groups. Also, the analysis of the posttest scores of the two groups show that there is no statistically significant difference in the performance of the two groups in the test (t = -0.53375, df = 54, p = 0.595699). The interpretation of this analysis is that since the p > 0.05, there is no statistically significant difference in the achievement of the experimental and the control groups in the post-test conducted; therefore the null hypothesis which states that “the use of CAI (independent variable) does not impact on the teaching and learning (students’ achievement) of Physical Science concepts (kinematics)” is upheld. Analysis of the interviews and classroom observation shows that teachers do not generally embrace the use of ICT in their teaching as a result of many factors one of which is the teacher‟s attitude and belief in the use of ICT. Teachers generally prefer to use the method they are accustomed to (teacher-talk) rather than learner-centred methods or exploring new grounds that ICT offers. Factors identified in the study as hampering the use of ICT by teachers are: Anxiety about the use of technology: Time factor Availability of technology Pre-service training The demand of the curriculum These factors are consistent with those identified by Stols (2008) and BECTA ICT Research (undated) in their review of what research says about barriers to the use of ICT in teaching.